Principles and practice of bookkeeping and accounts - Vickery, Bertram George; Mendes, B. (London, Cassell; St. Albans, Donnington Press, 1973)
The primary objective of this book is to guide students who are preparing for professional examination in book-keeping and accountancy.
Includes index
mf 13/09/2018
Loans
Keywords: Accounting; Bookkeeping